ASPEK SOSIAL EKONOMI KERAGAMAN HAYATI - LIES ANGGRENI, I GUSTI AYU AGUNG (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
People wherever they are living, are influenced by biotic and abiotic factors. Total of living organisms from single cell organism such as bacteria to higher level organisms such as various plants and animals is known as biological diversity or biodiversity. Biodiversity gives opportunities to people to develop their knowledge and technologies to utilize biodiversity for their daily lives such as food, medicines, industrial goods and housing. Thus, many aspects of people lives are directly or indirectly influenced by biodiversity.
Keywords: Daily Lives, Biodiversity